A Analisis Value Chain Industri Ritel - riyadi, taufan; Franciskus Antonius Alijoyo (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
A Value chain is one of the tools used to analyze competitive advantages and then be able to find ways to improve them. Retail is the final chain of distribution channels that bridges between producers and consumers in the sale of a product or service. Indostation is a retailer that will be the object of research. This Indostation is in Karawang Regency. The research method used is a descriptive method using data obtained through field observations, interviews and documentation. The results of this research analysis show that Indostation is advised to increase product variations, this will make it easier for customers to find the items they want, detail SOPs and provide the best service for customers